Diplomatic Immunity: Diplomatic Vehicles on Diplomatic Missions - Kusuma, Winanda; Situmorang, Ave Agave Christina; Permatasari, Bunga (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
ABSTRACT:Diplomatic law is an international custom that has been codified to facilitate the implementation of diplomatic duties. Diplomatic representatives in the receiving country are in a situation assigned by the sending country as an official task executor in the receiving country. conceptual thinking results in the section. Based on the provisions contained in the 1961 Vienna Convention, diplomatic representatives who carry out duties in the receiving country have the right to immunity and privileges. Diplomatic immunity is basically an international custom of not being able to be disturbed by someone who officially holds diplomatic office in carrying out duties as a representative of a foreign power. Protection of diplomatic representatives includes diplomatic support facilities such as diplomatic vehicles as a standard of diplomatic behavior between countries that have diplomatic relations, diplomatic facilities are used effectively for the interests of the sending country's duties in carrying out diplomatic functions. This is stated in the Functional Necessity theory. The approach method used is normative juridical, namely legal research carried out by examining library materials and statutory regulatory documents. The normative juridical approach method in this study focuses on determining diplomatic immunity, especially diplomatic vehicles in carrying out diplomatic immunity. Diplomatic immunity is the inviolability of a person officially holding diplomatic representation in carrying out the duties of a representative of power. The rules as a receiving country to strengthen and prevent the misuse of the Convention rules. Technical rules in continuing to implement the principle of reciprocity and mutual consent that have diplomatic relations.ABSTRAK:Hukum diplomatik merupakan kebiasaan internasional telah dikodifikasi untuk memberikan kemudahan dalam pelaksanaan tugas diplomatik. Perwakilan diplomatik pada negara penerima berada dalam situasi ditugaskan oleh negara pengirim sebagai pelaksana tugas resmi di negara penerima. hasil pemikiran konseptual dalam bagian. Berdasarkan ketentuan yang ada dalam Konvensi Wina 1961, perwakilan diplomatik yang menjalankan tugas di negara penerima memiliki hak kekebalan dan keistimewaan. Kekebalan diplomatik pada dasarnya suatu kebiasaan internasional atas tidak dapat diganggu seorang secara resmi mengemban pejabat diplomatik dalam menjelankan tugas sebagai perwakilan kekuasaan asing (foreign power). Perlindungan terhadap perwakilan diplomatik termasuk fasilitas pendukung diplomatik seperti kendaraan diplomatik sebagai standar prilaku diplomatik antara negara yang memiliki relasi diplomatik, fasilitas diplomatik digunakan secara efektif untuk kepentingan tugas negara pengirim dalam menjalan fungsi diplomasi. Hal ini yang tertuang dalam teori Functional Necessity. Metode pendekatan yang digunakan yuridis normatif yaitu penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka dan dokumen peraturan perundang-undangan. Metode pendekatan yuridis normatif pada peneliian ini memiliki fokus untuk mengetahui kekebalan diplomatik khususnya mobil diplomatik dalam menjalankan kekebalan diplomatic. Kekebalan diplomatic merupakan tidak dapat diganggu seorang secara resmi mengemban perwakilan diplomatik dalam menjalankan tugas perwakilan kekuasaan. Aturan sebagai negara penerima untuk memperkuat dan pencegahan atas salah penggunaan aturan Konvensi. Aturan teknis dalam tetap melaksanakan dengan asas resiprositas dan mutual consent yang memiliki relasi diplomasi.